Study of the sensitisation process of a duplex stainless steel (UNS 1.4462) by means of confocal microscopy and localised electrochemical techniques. (May 2015) - Leiva-García, R.; Fernandes, J.C.S.; Muñoz-Portero, M.J.; García-Antón, J.
Highlights: Morphological changes during heat treatments produce volumetric variations on the surface. Sensitised Alloy 900 presents a more defective passive film. The sensitised specimens present lower polarisation resistance. The sensitised samples present higher activity on their surface. Abstract: When duplex stainless steels are heated, they can become sensitised and intermetallic phases can appear. In this work, samples of duplex stainless steel, UNS 1.4462, have been heated (850 °C for 1 and 2 h) in a heating unit that can be accommodated to a confocal microscope in order to study the morphological changes in-situ. The electrochemical behaviour of the samples has been analysed by means of conventional and localised electrochemical techniques. According to the results, there is a general decrease in the steel resistance to localised corrosion; this decrease can be related to defects in the formed passive film.